Nirmatrelvir/Ritonavir for hemodialysis patients with COVID-19 - Lu, Jiayue; Cai, Hong; Hao, Yujun; Lin, Zhang; Liu, Shang; Zhan, Yaping; Ding, Li; Huang, Meilan; Li, Zhenyuan; Xu, Lan; Yan, Xiujuan; Yang, Li; et al. (Frontiers in Pharmacology, 2023)
Background: Hemodialysis patients have a high risk of severe /critical COVID-19 and related high mortality, but nirmatrelvir/ritonavir is not recommended for hemodialysis patients with COVID-19 infection because of lack of evidence of safety. Objectives: Our study aims to evaluate the minimum plasma concentration (Cmin) of nirmatrelvir and its safety of different doses of nirmatrelvir/ritonavir in hemodialysis patients with mild COVID-19. Method: This was a prospective, two step, nonrandomized, open-label study. Participants were treated with nirmatrelvir 150mg or 300mg once a day (another 75mg or 150mg supplied after hemodialysis) and ritonavir 100mg twice daily for 5 days, respectively. The primary outcome was the safety of nirmatrelvir/ritonavir, including the Cmin of nirmatrelvir and the number of adverse events(AE). The secondary outcome was the time of viral elimination in hemodialysis patients. Results: Adverse events were happened in 3 and 7 participants in the step 1 and step 2 group, respectively(P=0.025). Among them, 2 and 6 participants were identified as drug-related adverse events(P=0.054). No SAE or liver function damage happened. The Cmin of nirmatrelvir in step 1 and step 2 group were 5294.65±2370.59 ng/mL and 7675.67±2745.22 ng/mL (P=0.125). Compared to hemodialysis patients without nirmatrelvir/ritonavir, there were no statistical differences in overall viral elimination time (P=0.232). Conclusions: In our study, two doses of nirmatrelvir/ritonavir appeared to be excessive for hemodialysis patients. Although all of the patients tolerated 5-day administration, nearly half of the patients experienced drug-related adverse events. In addition, the medication group did not show a significant advantage in the time of viral elimination.